Higgs scalar potential coupled to gravity in the exponential parametrization in arbitrary gauge - Ohta, Nobuyoshi; Yamada, Masatoshi (Physical review, 2022)
We study the parametrization and gauge dependences in the Higgs field coupled to gravity in the context of asymptotic safety. We use the exponential parametrization to derive the fixed points for the cosmological constant, Planck mass, Higgs mass and its coupling, keeping arbitrary gauge parameters α and β, and compare the results with the linear split. ...